Clinical Guide to Assessment and Treatment of Communication Disorders - Prelock, Patricia A. (Best Practices in Child and Adolescent Behavioral Health Care,, 2018)
This book examines the typical pattern of communication development in children and adolescents to enable primary care physicians as well as other clinicians, therapists, and practitioners to assist parents in making informed decisions based on current research. It offers an overview of communication disorders in children and adolescents that typically present before adulthood. The book describes current assessment, diagnostic procedures, and evidence-based interventions. Chapters outline the standard course of speech milestones and ages to begin screening for deficits and their risk factors. Subsequent chapters review best practices for every aspect of treatment, including care planning, discussing disorders and interventions with parents, making referrals, and collaborating with other providers. The book also discusses evidence-based interventions for specific disorder types such as language impairment, stuttering, language disabilities, and hearing impairment. In addition, the book offers guidance on how to speak about care planning as well as quality of life issues related to communication disorders with other caregivers and parents. Featured topics include: Screening and identification procedures of communication disorders. Key elements to providing family-centered care. Common causes, assessment, and treatment of specific language impairment (SLI) in children. Hearing loss and its impact on the development of communication in children. Attention deficit/hyperactivity disorder (ADHD) and the role of attention in the development of language in children. Communication development in children with autism spectrum disorder (ASD). The Clinical Guide to Assessment and Treatment of Communication Disorders is a must-have resource for clinicians and related professionals, researchers and professors, and graduate students in the fields of child, school, and developmental psychology, pediatrics and social work, child and adolescent psychiatry, primary care medicine, and related disciplines.